ANATOMICAL-BIOMECHANICAL PECULIARITIES, PATHOGENESIS, CLINICAL FEDATURES AND DIAGNOSIS OF ILIOLUMBAR LIGAMENT SYNDROME (LITERATURE REVIEW) - Golka, Grygorii; Istomin, Dmytro; Istomin, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Low back pain is the most widespread manifestation of pathology in the locomotor system. This pain has a multifactorial nature and in a number of cases can be caused by ligament defects in the lumbosacral region, particularly in the iliolumbar ligaments. Objective. To find out the modern trends in the development, clinical manifestation and diagnosis of iliolumbar ligament (ILL) syndrome based on the analysis of scientific-medical information. Results. ILL syndrome is characterized by variability of its form, attachment sites and even number. It has been revealed that ILL’s play an important biomechanical role in providing of stability in the frontal plane on the level of LV vertebra, and in the horizontal plane they restrict rotation of LІV with respect to the pelvis. Asymmetry of the spatial orientation of ILL causes an increased risk of formation of disc herniation in LІV–SІ. Under the effect of overloads ILL’s develop structural changes or damages, whose risk increases with age. Diagnostic algorithms usually provide use of physical and radial techniques for revealing of ILL damages. Difficulties in physical diagnosis and blocking of ILL syndrome are caused by their insufficient specificity. Also rather weak is an association between pain manifestations in the low back and results of radiological examinations. CT and MRI make it possible to visualize ILL’s, but so far these opportunities do not give too much for practice because of absence of any signs, whose relationship with the appearance and dynamics of low back pain would be doubtless. Ultrasound examination is a more informative method for instrumental diagnosis of ILL syndrome. Conclusions. Development of provocative tests and therapeutic-diagnostic blocks, which hold on the principles of evidence-based medicine, is a promising trend in improving diagnosis of ILL syndrome. Biochemical criteria for revealing and monitoring ILL pathology and their correlation with sonographic characteristics of different stages in the development of ligamentopathy require specification.